Evolutionary Diversity of the Mitochondrial Calcium Uniporter - Bick, Alexander G.; Calvo, Sarah E.; Mootha, Vamsi K. (Science (American Association for the Advancement of Science), 2012)
Phylogenetic analysis of the mitochondrial calcium transporter shows that it was a feature of early eukaryotes. Calcium uptake into mitochondria occurs via a recently identified ion channel called the uniporter. Here, we characterize the phylogenomic distribution of the uniporter’s membrane-spanning pore subunit (MCU) and regulatory partner (MICU1). Homologs of both components tend to co-occur in all major branches of eukaryotic life, but both have been lost along certain protozoan and fungal lineages. Several bacterial genomes also contain putative MCU homologs that may represent prokaryotic calcium channels. The analyses indicate that the uniporter may have been an early feature of mitochondria.